Electrochemical Synthesis of Dibenzothiophene S,S-Dioxides from Biaryl Sulfonyl Hydrazides - Yasuyuki OKUMURA; Eisuke SATO; Koichi MITSUDO; Seiji SUGA (Electrochemistry, 2023)
The electrochemical synthesis of dibenzothiophene S,S-dioxides was achieved by the anodic oxidation of biaryl sulfonyl hydrazides. The use of Bu4NOTf as the electrolyte in HFIP/CH3NO2 (15 : 1) is essential. Several biaryl sulfonyl hydrazides followed by dibenzothiophene S,S-dioxides under mild electrochemical conditions. Control experiments and density functional theory calculations suggested that the electrooxidation of biaryl sulfonyl hydrazides would generate sulfonyl radicals or sulfonyl cations which were converted to dibenzothiophene S,S-dioxides.